The world of Velazquez, 1599-1660 - Brown, Dale; Time-Life Books (Amsterdam, [Netherlands] Time-Life Books, Inc., 1969)
Surveys the life, work and times of Diego de Silva Velazquez, the master 17th century Spanish painter.
The Lure of Madrid -- Beginning with Success -- The Royal Pleasures -- An Age of Giants -- The King Takes Command -- The Spain of Many Sorrows -- An End to Glory.
Includes bibliographical references (page 187) and index.
Keywords: Velâazquez, Diego -- 1599-1660.